Different yet similar: a study on Mongindong performed by diris, gustimin, pariama and tulai from Murok Village and Baba Village on the Labuk River, Sabah - Ang, Susan Ngar Jiu; Chan, Cheong Jan (Universiti Putra Malaysia Press, 2010)
The oral traditions of the Dusun Labuk include tangon, runsai, mongindong, mansuak, and kurilang. Mongindong [cradle song] is typologically informal yet functionally important in the traditional daily life of the Dusun Labuk. Seven mongindong were collected from four Dusun Labuk community members in Beluran, located in the east part of Sabah, Malaysia. It is important to note that the informants were reluctant to perform more than one mongindong for documentation purpose because they perceive that each of them owns only one mongindong, and therefore, two mongindong, although different in musical structure, are perceived as “sama” [the same] when they are performed by one informant. Furthermore, under certain circumstances, the informants perceive the mongindong performed by one person is “sama” [the same] as the mongindong which is performed by the other person. However, by viewing the tune and text of each collected mongindong, the researcher perceives each mongindong to be different from one another. Taking this into consideration, this paper describes the mongindong of the Dusun Labuk and suggests a possible way to analyse them. Findings from the analysis lead to an understanding of the similarity between the mongindong held by the informants. Nevertheless, further study on the culture of Dusun Labuk and the community members’ knowledge of oral traditions is necessary for a deeper understanding of mongindong.